The Challenged Sense of Belonging Scale (CSBS): a Validation Study in English, Arabic, and Farsi/Dari among Refugees and Asylum Seekers in Germany - Lukas M. Fuchs; Jannes Jacobsen; Lena Walther; Eric Hahn; Thi Minh Tam Ta; Malek Bajbouj; Christian von Scheve (Measurement Instruments for the Social Sciences, 2021)
This study introduces and investigates the validity of a brief scale measuring a challenged sense of belonging. The sense of belonging as well as challenges to this sense are important, albeit neglected aspects of social integration and of significance to migration and refugee studies as well as to virtually all other social science contexts. Assessing a challenged or eroded sense of belonging provides important insights into how individuals relate to their environment and whether they feel socially connected or disconnected from it. The construct goes beyond national or cultural identity, instead emphasizing the dynamic processes of emotional attachment. Reviewing the substantial theoretical literature on belonging, we identify four of its key elements: connection, participation, identification, and congruence. Drawing on existing measurement instruments, we propose a brief Challenged Sense of Belonging Scale (CSBS) that addresses each of the four elements and investigate its validity in a unique, multi-lingual random sample of 3783 adult refugees in Germany from various national and cultural backgrounds. We provide evidence for the scale's validity separately for three main survey languages (English, Arabic, Farsi/Dari) using confirmatory factor analysis, a test of measurement invariance, item test and rest correlations, and correlation analysis to explore convergent validity. Our findings suggest that the scale is a suitable instrument for the assessment of a challenged sense of belonging in a heterogeneous population of refugees.
Additional information: Open Access funding enabled and organized by Projekt DEAL.
Keywords: 330; Sense of belonging; Refugee; Challenged Sense of Belonging Scale; CSBS; Scale validation; Integration; Acculturation; IAB-BAMF-SOEP